2021
DOI: 10.2514/1.j059661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three-Dimensional Geometry on Harmonic Gust–Airfoil Interaction

Abstract: Two-dimensional (2D) strip-theory modelling of unsteady gust-aerofoil interaction is standard practice in many industrial applications, but the limits of applicability of 2D unsteady flow modelling on 3D wing and rotor geometries are not well understood. This paper investigates the effects of 3D geometry features, such as finite span, taper, sweep and rotation, on the unsteady lift response to gusts, and the flow-physical differences between 2D and 3D geometries in unsteady flow. A frequency-domain inviscid vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 29 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…3D effects were most significant near the blade tips, at low reduced frequencies and at low aspect ratios. Smyth et al [11] arrived at similar conclusions after carrying out a parametric study of 3D geometry effects in unsteady flow, using an inviscid 3D vortex lattice model. They found that aspect ratio effects largely determined the degree of 3D response, including for a rotor geometry.…”
Section: D Effectsmentioning
confidence: 61%
See 2 more Smart Citations
“…3D effects were most significant near the blade tips, at low reduced frequencies and at low aspect ratios. Smyth et al [11] arrived at similar conclusions after carrying out a parametric study of 3D geometry effects in unsteady flow, using an inviscid 3D vortex lattice model. They found that aspect ratio effects largely determined the degree of 3D response, including for a rotor geometry.…”
Section: D Effectsmentioning
confidence: 61%
“…For steady or quasi-steady flow, the impact of streamwise tip vortices on tidal turbines can be accounted for by tip-loss corrections (e.g., the commonly used Prandtl correction [12]). However, Smyth et al [11] demonstrated that the influence of the streamwise wake vortices changes substantially in unsteady flow conditions. As such, due to both the finite nature of the spanwise wake vorticity and the unsteady nature of the streamwise wake vorticity, the applicability of the Theodorsen function to tidal turbines is called into question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in references [16,29] have shown that when aspect ratio or reduction frequency is large enough, 2D and 3D results will tend to be consistent. Therefore, the expression of the circulation correction factor in this paper is given as follows:…”
Section: Circulation Correction Factormentioning
confidence: 93%
“…In theory, the wake vorticity of a wing with finite span can be divided into the streamwise vorticity and the spanwise vorticity [16]. For steady flow, the spanwise wake vorticity doesn't exist and the streamwise vorticity remains unchanged.…”
Section: Introductionmentioning
confidence: 99%